3x(4x-1)-4x(2x-3)-1=5+2x(2x+3)

Simple and best practice solution for 3x(4x-1)-4x(2x-3)-1=5+2x(2x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x(4x-1)-4x(2x-3)-1=5+2x(2x+3) equation:


Simplifying
3x(4x + -1) + -4x(2x + -3) + -1 = 5 + 2x(2x + 3)

Reorder the terms:
3x(-1 + 4x) + -4x(2x + -3) + -1 = 5 + 2x(2x + 3)
(-1 * 3x + 4x * 3x) + -4x(2x + -3) + -1 = 5 + 2x(2x + 3)
(-3x + 12x2) + -4x(2x + -3) + -1 = 5 + 2x(2x + 3)

Reorder the terms:
-3x + 12x2 + -4x(-3 + 2x) + -1 = 5 + 2x(2x + 3)
-3x + 12x2 + (-3 * -4x + 2x * -4x) + -1 = 5 + 2x(2x + 3)
-3x + 12x2 + (12x + -8x2) + -1 = 5 + 2x(2x + 3)

Reorder the terms:
-1 + -3x + 12x + 12x2 + -8x2 = 5 + 2x(2x + 3)

Combine like terms: -3x + 12x = 9x
-1 + 9x + 12x2 + -8x2 = 5 + 2x(2x + 3)

Combine like terms: 12x2 + -8x2 = 4x2
-1 + 9x + 4x2 = 5 + 2x(2x + 3)

Reorder the terms:
-1 + 9x + 4x2 = 5 + 2x(3 + 2x)
-1 + 9x + 4x2 = 5 + (3 * 2x + 2x * 2x)
-1 + 9x + 4x2 = 5 + (6x + 4x2)

Add '-4x2' to each side of the equation.
-1 + 9x + 4x2 + -4x2 = 5 + 6x + 4x2 + -4x2

Combine like terms: 4x2 + -4x2 = 0
-1 + 9x + 0 = 5 + 6x + 4x2 + -4x2
-1 + 9x = 5 + 6x + 4x2 + -4x2

Combine like terms: 4x2 + -4x2 = 0
-1 + 9x = 5 + 6x + 0
-1 + 9x = 5 + 6x

Solving
-1 + 9x = 5 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-1 + 9x + -6x = 5 + 6x + -6x

Combine like terms: 9x + -6x = 3x
-1 + 3x = 5 + 6x + -6x

Combine like terms: 6x + -6x = 0
-1 + 3x = 5 + 0
-1 + 3x = 5

Add '1' to each side of the equation.
-1 + 1 + 3x = 5 + 1

Combine like terms: -1 + 1 = 0
0 + 3x = 5 + 1
3x = 5 + 1

Combine like terms: 5 + 1 = 6
3x = 6

Divide each side by '3'.
x = 2

Simplifying
x = 2

See similar equations:

| 2,5x-(9-3x)=5x+(-4) | | 2,5-(9-3x)=5x+(-4) | | 5x(-3+5)= | | 72x^2-29x+1= | | x+38=190 | | 8-6p=62 | | 2x^2+12x+3=0 | | 4p+10=94 | | 8x-6+2x=13+5 | | 8*x+150*(480-x)=51000 | | 3.50x=150 | | 41-2t=17 | | ln(2x-5)=8 | | 1-2t=3 | | 4(x-3)=-9 | | 4(x-2)=2(x-1) | | 5t^2+4t-1= | | -4=6(x-2)-x | | -4(3n+1)=4 | | 91-6x=12x+23 | | 2x=8+8 | | 13-9x=40-16x | | -2*2f*3g=0 | | 33x-33=33 | | D=rt+5 | | 4x^2-15=123 | | 2x+48=678 | | 8ab=c | | y(1+0.5625)=112.5 | | 6=10h+36 | | X^2-3x=o | | 181+3m=1 |

Equations solver categories